Square Dual-Mode Quasi-Elliptic Bandpass Filter with Wide Upper Stopband - Ma, Y.; Che, W.; Feng, W.; Chen, J.-X. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A square dual-mode quasi-elliptic bandpass filter (BPF) with a wide stopband is proposed. To realize the quasi-elliptic response and harmonic suppression for the filter, the inductive source-load coupling is introduced. To achieve wider stopband suppression, the open-circuited stubs are adopted. A demonstration filter with 3-dB fractional bandwidth (2.84 GHz - 3.28 GHz) about 14.3 % has been designed, fabricated, and measured. Simulated and measured results indicate that the proposed filter can effectively suppress 6th harmonic response referred to a suppression degree of 16.5 dB.